Unraveling the Oncogenic Characteristics of the Cytolinker, Plectin, in Esophageal Squamous Cell CarcinomaSummary - Lili Qiao; Yuanyuan Hu; Lei Xu; Guodong Deng; Xiaohong Yu; Wei Zheng; Yanan Yang; Hui Yuan; Wei Jiang; Xiying Yu (Cellular and Molecular Gastroenterology and Hepatology, 2025)
Background & Aims: Tissue mechanics involved in carcinogenesis by regulating cell morphology and structure, cell-cell, and cell-extracellular matrix (ECM) interactions are not fully understood. Plectin, a cytolinker and a critical component of the cell-ECM adhesion complex hemidesmosome (HD), plays an important role in the regulation of epithelial tissue mechanics, but its functions in carcinogenesis remain elusive. Methods: We used cellular and molecular methods and multiple systems, including a 2-dimensional (2-D) esophageal keratinocyte Ca2+-dependent differentiation system, a 3-dimensional (3-D) esophageal keratinocyte organoid system, and tissue samples of normal rat and human esophageal stratified squamous epithelium (SSE), N-nitroso-N-methylbenzylamine (NMBzA)-induced rat esophageal squamous cell carcinoma (ESCC), and human ESCC, to determine the role(s) of plectin in regulating SSE homeostasis and ESCC carcinogenesis. Results: We show that plectin is ubiquitously expressed in all proliferative and differentiative cell types in esophageal SSE. However, the localization of plectin in different cell types is controlled by plectin crosslinking to different macromolecular structures, such as HD, desmosome (DSM), and cytoskeletal filaments, and its expression is regulated by the ESCC oncogenic drivers and transcription factors, p63 and/or Notch1. Plectin functions by coupling plectin-associated HD, DSM, and cytoskeletal components together with plectin regulators p63 and Notch1, to maintain cell anchorage, proliferation/differentiation, and stratification of esophageal SSE tissue homeostasis. Perturbation of plectin expression and localization leads to the disruption of SSE homeostasis and the involvement in ESCC carcinogenesis. Conclusions: Plectin is involved in maintaining SSE homeostasis, and misexpression of plectin through its genetic alterations or transcriptional dysregulations perturbs the compositions, stoichiometries, and localizations of plectin, HD, DSM, and the cytoskeleton underlying the oncogenic characteristics of plectin.